Identification of effective plant extracts against candidiasis: an in silico and in vitro approach - V. Anantha Bhairavi; S. L. Vidya; R. Sathishkumar (SpringerOpen, 2023)
Abstract Background Globally, millions of people suffer from repeated fungal infections affecting the skin, keratinized tissues, and mucosal membranes. Approximately 1.7 million cases result in death with an elevated incidence rate among immunocompromised people that may later result in severe infections. Among the causative agents, Candida albicans are the most prevalent fungi inducing subcutaneous to invasive candidiasis. Although they are commensals in human body alteration in gut or prolonged treatments results in candidiasis. Several virulence proteins of C. albicans are involved in infections and secreted aspartic proteases2 (SAP2) plays an important role among them by causing damage to the reconstituted human epithelium. In the present study, phytochemicals from Heliotropium indicum, Grona triflora, Ziziphus mauritiana, Atalantia racemosa, Coccinia grandis, Caryota urens, Aristolochia bracteolata, Evolvulus alsinoides, Pyrus communis and Commelina benghalensis were studied against SAP2 with the help of bioinformatic tools to understand their binding efficiency. Results The phytochemical structures were retrieved from PubChem database and the target protein structure was retrieved from PDB database with ID:3PVK. ADME profiling for phytochemicals was performed with Qikprop module, followed by docking with protein using Schrodinger software. Docking studies showed that Indicine-N-Oxide from H. indicum scored the significant glide score of − 5.54 kcal/mol. Finally, antifungal studies against C. albicans were conducted using several extracts of plants containing phytochemicals with considerable glide scores on docking studies. The Ethyl acetate leaf extract of H. indicum prominently inhibited the fungal growth when compared with the control. Conclusion Identification of effective therapeutic candidates for the treatment of fungal infection is facilitated by the potential of H. indicum to hinder fungal growth and the interaction of their phytocompounds with fungal targets paves a way for developing a novel drug.